Tails of Two Cities: Age and Wounding Are Associated With Carriage of Leptospira interrogans by Norway Rats (Rattus norvegicus) in Ecologically Distinct Urban Environments - Minter, Amanda; Himsworth, Chelsea G.; Byers, Kaylee A.; Childs, Jamie E.; Ko, Albert I.; Costa, Federico (Frontiers in Ecology and Evolution, 2019)
Leptospirosis is a zoonotic disease for which rats are the primary reservoir in urban environments. It is transmitted from rats to people via urine, and is responsible for significant human morbidity and mortality in under-resourced settings. To mitigate the risks posed to people, it is important to understand the ecology of the causative agent Leptospira interrogans. The overarching objective of this study was to compare L. interrogans carriage in urban Norway rats in two ecologically distinct urban environments. We trapped Norway rats (Rattus norvegicus) in Vancouver, Canada (N = 525) and Salvador, Brazil (N = 433) to evaluate whether rat characteristics (i.e., sex, weight, sexual maturity, pregnancy, and the presence of wounds) and location of capture were associated with L. interrogans status. Using generalized linear mixed models to control for clustering by trapping location, we found a greater prevalence of L. interrogans in Salvador (79%) than in Vancouver (12%), and greater spatial heterogeneity in pathogen prevalence in Vancouver than in Salvador. In both locations, we found that older rats and rats with more bite wounds had greater odds of L. interrogans carriage, although wounding influenced pathogen status more for younger animals. Additionally, we found that juvenile rats in Salvador were more likely to leave the nest infected with L. interrogans than were rats in Vancouver, suggesting that potential differences in early-life transmission dynamics exist between the two locations. Together, these results elucidate both general L. interrogans ecology, as well as the importance of geographical location in determining transmission among rats.